The compact triply eclipsing triple star TIC 209409435 discovered with TESS. Issue 4 (24th June 2020) - Borkovits, T; Rappaport, S A; Tan, T G; Gagliano, R; Jacobs, T; Huang, X; Mitnyan, T; Hambsch, F-J; Kaye, T; Maxted, P F L; Pál, A; Schmitt, A R
ABSTRACT: We report the discovery in TESS Sectors 3 and 4 of a compact triply eclipsing triple star system. TIC 209409435 is a previously unknown eclipsing binary with a period of 5.717 d, and the presence of a third star in an outer eccentric orbit of 121.872-d period was found from two sets of third-body eclipses and from eclipse timing variations. The latter exhibits signatures of strong third-body perturbations. After the discovery, we obtained follow-up ground-based photometric observations of several binary eclipses as well as another of the third-body eclipses. We carried out comprehensive analyses, including the simultaneous photodynamical modelling of TESS and ground-based light curves (including both archival WASP data, and our own follow-up measurements), as well as eclipse timing variation curves. Also, we have included in the simultaneous fits multiple star spectral energy distribution data and theoretical PARSEC stellar isochrones. We find that the inner binary consists of near twin stars of mass 0.90 M⊙ and radius 0.88 R⊙ . The third star is just 9 per cent more massive and 18 per cent larger in radius. The inner binary has a rather small eccentricity, while the outer orbit has e = 0.40. The inner binary and outer orbit have inclination angles within 0.1° and 0.2° of 90°, respectively. The mutual inclination angle is ≲1/4°. All of these results were obtained without radial velocity observations.